2023
DOI: 10.1186/s12912-023-01194-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the transition to adulthood of Korean young adults with spina bifida: a qualitative study

Abstract: Background Transition to adulthood to live independently while self-managing health and daily life without parental help is crucial for young adults with chronic conditions. Despite its importance as a precursor to effectively managing lifelong conditions, little is known about the experiences of young adults with spina bifida (SB) in transition to adulthood in Asian countries. This study aimed to explore the experiences of Korean young adults with SB to identify the facilitators or barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Although not statistically significant due to very large standard deviation, these results suggest that children with SB with foot deformities can feel notably limited in choosing the shoes they want. A study on the experience of young adults with SB in Korea found that wearing orthosis and lower limb appearance had a negative effect on body image and psychosocial well-being [ 22 , 23 ]. This suggests that concerns about appearance and body image related to lower extremity deformities or orthosis use may be as important as mobility problems for children with SB.…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant due to very large standard deviation, these results suggest that children with SB with foot deformities can feel notably limited in choosing the shoes they want. A study on the experience of young adults with SB in Korea found that wearing orthosis and lower limb appearance had a negative effect on body image and psychosocial well-being [ 22 , 23 ]. This suggests that concerns about appearance and body image related to lower extremity deformities or orthosis use may be as important as mobility problems for children with SB.…”
Section: Discussionmentioning
confidence: 99%